TOURISM MARKETING COMMUNICATION STRATEGY FOR TOURIST VILLAGES IN SUBANG REGENCY - Iing Saefudin (GoAcademica Research dan Publishing, 2025)
This study aims to analyze the tourism marketing communication strategies implemented by tourism village managers in Subang Regency to increase tourist visits. With the rapid development of rural-based tourism, this study focuses on the effectiveness of communication channels, the promotional mix, and local community participation. This study used a qualitative descriptive approach. The results indicate that the current marketing communication strategy has only entered the initial digital transition phase through the use of Instagram and TikTok, but has not yet implemented the principles of Integrated Marketing Communication. Digital promotional activities remain sporadic without a content calendar, and neglect the functions of public relations and direct marketing, resulting in managers relying heavily on word-of-mouth. Marketing effectiveness is hampered by structural factors (blank spots and damaged road access) and cultural factors (low digital literacy among local managers). Furthermore, the dynamics of multi-stakeholder synergy (pentahelix) have not been harmonious due to sectoral egos between the government, academia, the private sector, and the media. This study reconstructs the need for the establishment of a regular communication coordination forum and a networking model to align the vision for sustainable regional tourism promotion.